Culinary tourism on the edge of Kali Code: Strategies for the development and empowerment of Kampung Surokarsan - Cininta, Mutiara; Tyas, Hari Saptaning (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
The government has constructed a robust embankment in Kampung Surokarsan, formerly a landfill, now providing a clearer view of Kali Code's banks. Nevertheless, residents have not yet tapped into the potential of Kali Code's surroundings for public or tourism purposes. In this densely populated area with predominantly self-employment, the